2023
DOI: 10.3390/plants12193395
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Characterization of Phosphate-Solubilizing Fungi and Their Effects on Coffee Plantations

Rosa María Arias,
Gabriela Heredia Abarca,
Yamel del Carmen Perea Rojas
et al.

Abstract: The use of phosphate-solubilizing fungi in coffee cultivation is an alternative to the use of traditional fertilizers. The objective of this study was to analyze the mechanisms involved in the phosphorus solubilization of fungal strains and to evaluate the effect of a phosphate-solubilizing strain on coffee plants. For this, phosphorus-solubilizing fungal strains were selected for evaluation of their solubilization potential and phosphatase activity. Coffee plants were inoculated in the field with a phosphate-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Meanwhile, it was also observed that Chaetomium, Talaromyces, and Rhizopus had higher abundances in T2 and T3. Fusarium, Talaromyces, and Rhizopus have been reported to have the phosphate-solubilizing capacity [32]. Wang [33] reported that healthy soil has higher abundances of beneficial microbes (Acremonium, Chaetomium), which can improve soil nutrients, promote plant growth, and control soil-borne diseases [34].…”
Section: Effect Of Tillage Depth On Tobacco-planting Soil Bacterial A...mentioning
confidence: 99%
“…Meanwhile, it was also observed that Chaetomium, Talaromyces, and Rhizopus had higher abundances in T2 and T3. Fusarium, Talaromyces, and Rhizopus have been reported to have the phosphate-solubilizing capacity [32]. Wang [33] reported that healthy soil has higher abundances of beneficial microbes (Acremonium, Chaetomium), which can improve soil nutrients, promote plant growth, and control soil-borne diseases [34].…”
Section: Effect Of Tillage Depth On Tobacco-planting Soil Bacterial A...mentioning
confidence: 99%